PERSEPSI MASYARAKAT DESA SAHAN TERHADAP SATUAN POLHUT REAKSI CEPAT (SPORC) (Perception Of Community Sahan Village Towards Satuan Polhut Reaksi Cepat (SPORC)) - Teterissa, Erwin Anton; Nurdjali, Bachrun; Zainal, Sofyan (Universitas Tanjungpura, 2013)
ABSTRACT Disturbance to protected areas Nyiut Mountain Nature Reserve from the village who lives close to the nature reserve, one of which is the village Sahan. People who want to meet the necessities of life to have to deal with SPORC Brigade Bekantan officers, so this study aims to determine the perception of community sahan village towards Satuan Polhut Reaksi Cepat (SPORC) activities in Nyiut Mountain Nature Reserve and to determine the relationship between the level of age, knowledge and cosmopolitan village with perception of community sahan village towards Satuan Polhut Reaksi Cepat (SPORC) activities in Nyiut Mountain Nature Reserve. The method used was a survey method with interview-assisted questionnaire. Determination of the number of respondents using Slovin formula and its determination by purposive sampling. Data analysis using Chi Square formula. Perception of community sahan village towards Satuan Polhut Reaksi Cepat (SPORC) activities in Nyiut Mountain Nature Reserve tend to be different. Data analysis showed 50.70% of the respondents are neutral, it is because they basically support the SPORC Brigade Bekantan activities that preserve Nyiut Mountain Nature Reserve but people also complained about the lack of SPORC Brigade Bekantan to dissemination and outreach to the community Sahan Village. Independent variables that have a real relationship / significant with the perception of community sahan village towards Satuan Polhut Reaksi Cepat (SPORC) activities in Nyiut Mountain Nature Reserve is the level of knowledge, whereas that does not have a real relationship / significant is the age level and the level of cosmopolitan society. Keywords: Perception, Sahan Village, SPORC Brigade Bekantan